The Impact of Governance Practices on Attaining Institutional Excellence (The International Journal for Scientific Research, 2025)
This study aims to investigate the impact of governance implementation on achieving institutional excellence, with a specific focus on the Ministry of Energy in the Kingdom of Saudi Arabia. The research adopts both the descriptive-analytical and inductive methodologies to analyze the current state of governance and excellence practices within the Ministry. A structured questionnaire was administered to employees, consisting of 25 questions divided into three sections: demographic data (5 questions), governance as the independent variable (10 questions), and institutional excellence as the dependent variable (10 questions).The findings indicate that the Ministry of Energy is committed to enhancing its governance-related capabilities among employees and is perceived by some as promoting fairness and integrity in rewards and incentives. These practices contribute positively to employee satisfaction and support the achievement of institutional excellence. Moreover, the Ministry benefits from strong leadership capable of guiding teams, seizing opportunities, and improving productivity. The study concludes that leveraging leadership competencies can foster strategic development, inter-team collaboration, and alignment with the Ministry’s overarching goals, ultimately reinforcing institutional excellence. It is recommended to focus on the continuous development of employees by increasing the number of specialized training courses in areas related to governance and institutional excellence. This can be achieved by recruiting certified and specialized trainers and ensuring that training content is regularly updated to reflect best practices and emerging trends.Moreover, it is important to provide employees with comprehensive information on institutional excellence models, such as the European Foundation for Quality Management (EFQM) Excellence Model. This can be facilitated through dedicated workshops aimed at familiarizing employees with these models and their underlying principles. Additionally, it is essential to develop clear and structured action plans that outline the specific steps required to implement institutional excellence standards effectively.
Keywords: Governance; Institutional Excellence; Principles of Governance; Stages of Institutional Excellence